Investigation of Emerging Memory Technologies Such as Resistive Ram and Phase-Change Memory for VLSI Applications - Kumar, P. Maniraj; Prasad, M. V. R. D.; Kavitha, P.; Munjal, Neha (2023 International Conference on Innovative Computing, Intelligent Communication and Smart Electrical Systems (ICSES), 2023)
TPC manufacturers have followed a very much organized order of memory arrangements since the innovation of the electrical PC and the Von Neumann model, obviously offsetting execution and limit with cost. With an end goal to address these issues and somewhat or totally supplant the current technologies, new ones have been examined and grown as of late, like resistive RAM (RRAM) and phase change memory (PCM). The attributes of state of the art memory technologies for VLSI applications, for example, resistive RAM and phase-change memory, are analyzed in this examination. The field of creating memory technologies is first given a fast framework. Conversation is had in regards to the RRAM's electrical properties, obstruction exchanging cycle, and material characteristics. Furthermore, various hardships are talked about, including perseverance, maintenance, homogeneity, and the effect of functional temperature and irregular message commotion (RTN). There is a portrayal of the RRAM's multi-facet cell (MLC) stockpiling capacities, which is attractive for arriving at high capacity thickness at a sensible cost. Different functional techniques for accomplishing reliable MLC activity have been offered, along with their fundamental actual components. A prologue to the subject of creating memory technologies is given in this paper. It is tended to how phase-change memory and RRAM vary as far as their electrical properties, opposition exchanging instrument, andmaterial piece. Moreover, various troubles are talked about, like power, maintenance, consistency, and the effect of functional temperature and irregular message commotion (RTN).